SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN KOKI MENERAPKAN METODE COMPOSITE PERFORMANCE INDEX - Adelina, Putri Dani; Waruwu, Fince Tinus; Ginting, Guidio Leonarde; Sianturi, Maringan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
The problems that occur in chef selection have been carried out by the Head of Chef and most likely not all criteria for lexis are made judged, sometimes only a few criteria are assessed. A good restaurant certainly needs to reconsider the chef who will be accepted according to predetermined criteria. The success of a restaurant business in the background of pengelolahan in it, including the selection of a good chef will encourage the success of the restaurant. In dealing with chef selection problems conducted by the Head of Chef, a decision support system can be developed in the face of chef acceptance selection problems, namely by using the Composite Performance Index method. The criteria that will be used as an assessment are the taste of cuisine, experience, speed, creativity, education, and cleanliness. For this reason, the author hopes that the application system for receiving chef selection decisions using the Composite Performance Index method can facilitate Fishermen's Restaurant in the chef's reception selection.Keywords: Decision Support Systems, Chefs, Restaurants, Composite Performance Index